2015
DOI: 10.1097/nmd.0000000000000371
|View full text |Cite
|
Sign up to set email alerts
|

Sex Bias in Classifying Borderline and Narcissistic Personality Disorder

Abstract: This study investigated sex bias in the classification of borderline and narcissistic personality disorders. A sample of psychologists in training for a post-master degree (N = 180) read brief case histories (male or female version) and made DSM classification. To differentiate sex bias due to sex stereotyping or to base rate variation, we used different case histories, respectively: (1) non-ambiguous case histories with enough criteria of either borderline or narcissistic personality disorder to meet the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 19 publications
3
7
0
Order By: Relevance
“…Our findings in males contribute to the literature on social isolation and behavioral outcomes as most of the previous studies focus on female mood disorders related to the pandemic and social isolation (Almeida et al, 2020; Wang et al, 2020). Our data are fairly consistent with studies that broadly analyze gender differences in typical traits in mental disorders, with a higher frequency of behavioral outcomes in males (Paris, 2007) although these series may have been influenced by bias (Braamhorst et al, 2015; Crosby & Sprock, 2004).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings in males contribute to the literature on social isolation and behavioral outcomes as most of the previous studies focus on female mood disorders related to the pandemic and social isolation (Almeida et al, 2020; Wang et al, 2020). Our data are fairly consistent with studies that broadly analyze gender differences in typical traits in mental disorders, with a higher frequency of behavioral outcomes in males (Paris, 2007) although these series may have been influenced by bias (Braamhorst et al, 2015; Crosby & Sprock, 2004).…”
Section: Discussionsupporting
confidence: 89%
“…Our findings in males contribute to the literature on social isolation and behavioral outcomes as most of the previous studies focus on female mood disorders related to the pandemic and social isolation (Almeida et al, 2020;Wang et al, 2020). Our data are fairly consistent with studies that broadly analyze gender differences in typical traits in mental disorders, with a higher frequency of behavioral outcomes in males (Paris, 2007) although these series may have been influenced by bias (Braamhorst et al, 2015;Crosby & Sprock, 2004) Our unique study design and population, located in one of the first global hotspots of the first wave of the COVID-19 pandemic, provided the opportunity to examine the impact of the pandemic related social isolation on healthy young adults. Our findings suggesting that males may be more vulnerable to the impacts of social isolation on rule breaking behavior could help direct targeted interventions.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, research has shown that the extent to which sex bias in diagnosis may occur is influenced by the ambiguity of the case. In a sample of trainee clinicians, Braamhorst et al (2015) presented participants with hypothetical case vignettes containing the following: non-ambiguous case histories with sufficient features of either BPD or NPD to meet the threshold for classification, and an ambiguous case containing subthreshold features of both NPD and BPD. Results showed that there was no effect of sex of patient when sufficient information was presented to correctly diagnose BPD and NPD.…”
Section: Narcissistic Personality Disorder In Femalesmentioning
confidence: 99%
“…Part of the sex differences in mental disorders’ prevalence may thus be due to sex bias in diagnostics (e.g., [ 13 15 ]), such as the tendency to focus on (sex) differences rather than on similarities [ 16 ], or to use sex-stereotyped definitions of mental disorders (e.g., [ 17 ]). Despite of these types of biases influencing reported figures and statistics, the literature is consistent in accepting the existence of sex differences in mental disorders’ prevalence as facts (e.g., [ 8 , 9 , 18 – 20 ]).…”
Section: Introductionmentioning
confidence: 99%